A New Anesthetic, Remimazolam, Is Useful in the Management of Anesthesia in Patients with Liver Cirrhosis - Anna Onoda; Yasuyuki Suzuki (Case Reports in Anesthesiology)
Background. Management of general anesthesia in patients with liver cirrhosis is challenging because it is difficult to maintain the circulation and concentration of anesthetics within a safe range. Unlike many other anesthetics, which are metabolized by cytochrome P450 enzymes, remimazolam is metabolized by carboxylesterase. In a liver cirrhosis model, cytochrome P450 activity is suppressed by approximately 30%; however, carboxylesterase activity is maintained at approximately 60%. Also, remimazolam is less likely to inhibit circulation. A 77-year-old woman was scheduled to undergo laparoscopic cholecystectomy. The patient was diagnosed with Child-Pugh B liver cirrhosis due to type C viral hepatitis. General anesthesia with remimazolam stabilized the intraoperative circulation and resulted in rapid postoperative awakening. Conclusion. We report a case in which a patient with Child-Pugh B cirrhosis was safely managed under general anesthesia using remimazolam during laparoscopic cholecystectomy.